Peningkatan Hasil Belajar Siswa Menggunakan Model Problem Based Learning di Kelas 5 Sekolah Dasar - Putri Septi Yanda; Mansurdin Mansurdin (Universitas Negeri Padang, 2023)
The learning outcomes obtained by students who are still low are the background of this research. This is caused by students being less motivated to participate in learning. By using the Problem-Based Learning (PBL) model, the research seeks to describe improvements in planning, implementation, and learning outcomes of integrated thematic learning. PTK is a type of research that combines qualitative and quantitative methods. The research was conducted in two cycles; The first cycle consisted of two meetings, while the second cycle only had one meeting. The results of the study revealed that the lesson plan observation results obtained an average score of 87.50 percent for the first cycle and rose to 92.85 percent for the second cycle in carrying out the proportion of teacher activity observations the first cycle averaged 84%, increasing to 92.85%. in the second cycle. In the second cycle, the percentage of students who achieved the average student aspect increased from 82.14 percent to 96.42 percent. In the first cycle, student learning outcomes had an average value of 72.3, but in the second cycle, it increased to 87.3. Therefore it can be concluded that the use of the Problem-Based Learning (PBL) model can improve student learning outcomes.